Is it possible to have freedom of expression? Religious Minorities' Perceptions of Social Media in Pakistan - Zubair Mahmood; Muhammad Jawed Aslam; Jamilah Ahmad (CoverAge: Journal of Strategic Communication, 2022)
This research article aims to understand that why social media is being perceived for freedom of speech by religious minorities in Pakistan. This qualitative study is based on four in-depth interviews of Christian activists in Pakistan. The study found that there are some crucial issues in giving media coverage to the religious minorities in Pakistan.The results demonstrate that religious minorities in Pakistan are facing segregations due to the prejudiced mindset of higher administration decisions, sponsors and lack of information with respect to religious minorities and their religious rituals. Besides, that absence of resistance from both minorities and larger part is playing the part in wrecking peace. The researchers found that English media whether print or electronic are giving adequate scope to the religious minorities in Pakistan. Furthermore, religious minorities in Pakistan are more inclined towards using social networking sites like Facebook to exercise their freedom of speech and expression as its more convenient in conveying the message without any mediated angling.